Reviews and Interviews - Fisiak, Tomasz; Pietrzak, Wit; Górny, Antoni; Majer, Krzysztof; Gaston, Bill; Blacker, Uilleam; Kosmalska, Joanna (Text Matters: A Journal of Literature, Theory and Culture, 2016)
Timeless Radcliffe: A Review of Ann Radcliffe, Romanticism and the Gothic (Cambridge: Cambridge UP, 2014) - Tomasz FisiakYeats’s Genres and Tensions: A Review of Charles I. Armstrong’s Reframing Yeats: Genre, Allusion and History (London and New York: Bloomsbury, 2013) - Wit PietrzakReview of Anna Pochmara’s The Making of the New Negro: Black Authorship, Masculinity, and Sexuality in the Harlem Renaissance (Amsterdam: Amsterdam UP, 2011) - Antoni Górny“Artful Exaggeration” - Krzysztof Majer (University of Łódź) Interviews Bill GastonTranscultural Theatre in the UK - Uilleam Blacker Talks to Joanna Kosmalska (University of Łódź)